2010
DOI: 10.1016/j.virol.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Classical swine H1N1 influenza viruses confer cross protection from swine-origin 2009 pandemic H1N1 influenza virus infection in mice and ferrets

Abstract: The hemagglutinin of the 2009 pandemic H1N1 influenza virus is a derivative of and is antigenically related to classical swine but not to seasonal human H1N1 viruses. We compared the A/California/7/2009 (CA/7/09) virus recommended by the WHO as the reference virus for vaccine development, with two classical swine influenza viruses A/swine/Iowa/31 (sw/IA/31) and A/New Jersey/8/1976 (NJ/76) to establish the extent of immunologic cross-reactivity and cross-protection in animal models. Primary infection with 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
6
25
0
Order By: Relevance
“…Therefore, a single infection with, and clearance of, a seasonal H1N1 virus can provide immunological protection from a lethal dose of the distantly related pandemic strain. This conclusion is in agreement with recently published work using different H1N1 virus strains in ferrets (39) and C57BL/6 mice (27,39) and with recent studies showing the ability of the commercial FluMist vaccine to protect C3H and C57BL/6 mice from future infection with the pandemic H1N1 virus (62).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, a single infection with, and clearance of, a seasonal H1N1 virus can provide immunological protection from a lethal dose of the distantly related pandemic strain. This conclusion is in agreement with recently published work using different H1N1 virus strains in ferrets (39) and C57BL/6 mice (27,39) and with recent studies showing the ability of the commercial FluMist vaccine to protect C3H and C57BL/6 mice from future infection with the pandemic H1N1 virus (62).…”
Section: Resultssupporting
confidence: 93%
“…Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
supporting
confidence: 58%
“…In addition, nasal symptoms such as sneezing or nasal discharge were not observed. This was consistent with the results from previous studies using ferrets of a similar age (45).…”
Section: Effectsupporting
confidence: 93%
“…Ferrets primed with the homologous CA/09 or NJ/76 virus served as a positive control, while the negative control was an influenza B virus (B/Mal) that would not cross-protect against influenza A virus infection (20). NJ/76, which caused limited infections in humans and never circulated among the general population, is a genetically and antigenically related swine origin H1N1 virus previously shown to protect against CA/09 virus infection (31,45).…”
Section: Virusesmentioning
confidence: 99%
“…There is circumstantial evidence from human studies and animal models that T cells recognizing conserved epitopes can mediate heterotypic immunity against divergent influenza virus strains in the absence of crossreactive NAbs (15)(16)(17)(18)(19)(20)(21)(22), though this concept has so far been tested directly only in mice (21). Accordingly, a number of studies have suggested that infection with seasonal influenza virus provides a level of protection against the swine-origin pandemic 2009 influenza virus (H1N1pdm) in the absence of NAbs, an effect which may be mediated by cross-reactive T cell responses (17,(23)(24)(25)(26)(27)(28). However, the degree to which T cells can mediate effective, longlived heterotypic immunity to influenza in humans remains unclear.…”
mentioning
confidence: 99%